Comparative Histological Analysis of Dentine-Derived Tooth Grafts in Maxillary vs Mandibular Socket Preservation: A Retrospective Study of 178 Cases - Elio Minetti; Francesco Gianfreda; Patrizio Bollero; Ciro Annicchiarico; Monica Daniele; Rossella Padula; Filiberto Mastrangelo (MDPI AG, 2024)
(1) Background: In recent years, there has been a growing interest in tooth-derived materials as valuable alternatives to synthetic biomaterials for preventing alveolar ridge dimensional changes. This study aimed to evaluate the histological and clinical differences between alveolar ridge preservation procedures in the maxilla and mandible using demineralized dentin treated with Tooth Transformer®. (2) Methods: A total of 178 patients in good general health were enrolled, with 187 post-extractive sockets lacking buccal and/or palatal bone walls. Alveolar socket preservation procedures and histological evaluations were performed. The sites were divided into two groups: Group A (99 mandibular samples) and Group B (108 maxillary samples). After 5 months (±1 month), single bone biopsies were performed for histologic and histomorphometric analysis. (3) Results: Clinical outcomes demonstrated a good healing of hard and soft tissues with an effective maintenance of bone architecture in both groups. Histomorphometric analysis revealed a total bone volume of 50.33% (±14.86) in Group A compared to 43.53% (±12.73) in Group B. The vital new bone volume was 40.59% (±19.90) in Group A versus 29.70% (±17.68) in Group B, with residual graft dentin material volume at 7.95% (±9.85) in Group A compared to 6.75% (±9.62) in Group B. (4) Conclusions: These results indicate that tooth-derived material supports hard tissue reconstruction by following the structure of the surrounding bone tissue. A 6.8% difference observed between the maxilla and mandible reflects the inherent disparities in natural bone structures in these regions. This suggests that the bone regeneration process after tooth extraction adheres to an anatomical functional pattern that reflects the specific bone characteristics of each area, thus contributing to the preservation of the morphology and functionality of the surrounding bone tissue.